SISTEM PENDUKUNG KEPUTUSAN PENENTUAN SISWA BERPRESTASI PADA SEKOLAH MENENGAH KEJURUAN NEGRI 02 KOTA TANGERANG SELATAN BERBASIS WEB MENGGUNAKAN METODE SIMPLE ADDITIVE - Muhammad Arif Prasetyo; Agung Perdananto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Determination of outstanding students plays an important role in the quality of schools. At SMK Negri 02 South Tangerang, the determination of outstanding students has not been maximized, because there is no special application that handles a decision support system for outstanding students. From the number of students can produce many spreadsheets and large capacity as well. With these problems, researchers will design a decision support system to determine outstanding students with a web-based system that uses the Simple Additive Weighting (SAW) method by taking from the criteria determined by the school, namely the average value of report cards, attendance and personality attitudes. With this system, it can make it easier for the school to determine outstanding students and make it easier to process the processing of high achieving students.